Human-Machine Collaboration as a Factor of Labour Productivity and Efficiency - Menshikov, Vladimir; Kokina, Irena; Komarova, Vera; Korshenkov, Evgeniy (European Scientific Journal, ESJ, 2020)
This article is aimed to give an empirical answer to the following research questions: 1) whether work as a type of activity and as a life value is losing its significance in the modern world; 2) whether human-machine collaboration (HMC) is a significant factor of labour productivity and efficiency. The authors suppose, that in the market economy labour productivity “merges“ with its efficiency – in contrast to a planned economy. Thus, it is possible to talk about “labour efficient productivity” or simply about labour productivity. The methods applied for empirical study are the following: analysis of statistics, regression analysis and correlation analysis. Eurostat and Latvia‘s statistics as well as data of the World Values Survey and data collected by the World Economic Forum and other international organsations. Results of the empirical research show that despite the increase in employment rate in the EU as a whole and in Latvia in particular, work as a type of activity and as a life value is losing its significance in the modern world. HMC empirically is measured by two indicators which show the potential of a country in HMC: digital skills of the population and ICT adoption. Results of the analysis show that HMC is a significant factor of labour productivity in the modern world, while various components of HMC have different significance in two groups of the world countries. In countries with a high potential of HMC, including Latvia, digital skills of the population is the determinant of labour productivity. In its turn, in countries with a low potential of HMC, the main factor of labour productivity is ICT adoption.